Wind Turbine Inverter Robust Loop-Shaping Control Subject to Grid Interaction Effects - Gryning, Mikkel P. S.; Wu, Qiuwei; Blanke, Mogens; Niemann, Hans Henrik; Andersen, Karsten P. H. (IEEE transactions on sustainable energy, 2016)
An H ∞ robust control of wind turbine (WT) inverters employing an inductor-capacitor-inductor (LCL) filter is proposed in this paper. The controller dynamics are designed for selective harmonic filtering in an offshore transmission network subject to parameter perturbations. Parameter uncertainty in the network originates from the grid and the number of WTs connected. Power converter-based turbines inject harmonic currents, which are attenuated by passive filters. A robust high-order active filter controller is proposed to complement the passive filtering. The H ∞ design of the control loop enables desired tracking with integral effect while bounding the induced change. The design was tested in an aggregated model of the London Array offshore wind power plant and compared with traditional Proportional-Integral (PI) controller designs. Robust stability and performance and a reduction of control effort by 25% are obtained over the full envelope of operation.